miR-149 Inhibits Non-Small-Cell Lung Cancer Cells EMT by Targeting FOXM1 - Yang Ke; Weiyong Zhao; Jie Xiong; Rubo Cao (Biochemistry Research International)
MicroRNAs (miRNAs) have been implied to play crucial roles for epithelial-to-mesenchymal transition (EMT) of non-small-cell lung cancer cells (NSCLC cells). Here we found that the expression of miR-149, downregulated in lung cancer, was inversely correlated with invasive capability and the EMT phenotype of NSCLC cells. miR-149 inhibited EMT in NSCLC cells. Furthermore, we demonstrated that miR-149 directly targeted Forkhead box M1 (FOXM1), and FOXM1 was involved in the EMT induced by TGF-β1 in A549 cells. Overexpression of FOXM1 restored EMT process inhibited by miR-149. Our work suggested that miR-149 might be an EMT suppressor in NSCLC cells.